The Influence of Stuttering Severity on Acoustic Startle Responses. - Ellis, John B.; Finan, Donald S.; Ramig, Peter R. (Journal of Speech, Language & Hearing Research, 2008)
Purpose: This study examined the potential impact of stuttering severity, as measured by the Perceptions of Stuttering Inventory (Woolf, 1967) on acoustic startle responses. Method: Three groups, consisting of 10 nonstuttering adults, 9-mild stutterering adults, and 11 moderate/severe stutterering adults; were presented with identical 95-dB acoustic stimuli to elicit acoustic startle responses across 10 trials. Electromyographic recordings of orbicularis occuli activity were used to measure individual acoustic startle responses. Results: Participant groups failed to exhibit statistically significant differences in initial acoustic startle response amplitude, mean acoustic startle response amplitude, habituation rates, and onset latency. Acoustic startle responses were characterized by high levels of variability across all participant groups but with highest levels of variability in the moderate/severe stuttering group. Conclusions: The current results suggest that stuttering severity, as measured in this study, does not effectively predict acoustic startle responses in groups of adults who stutter. Reprinted by permission of the publisher.